PENANAMAN SIKAP PEDULI LINGKUNGAN DAN SIKAP ILMIAH SISWA SEKOLAH DASAR MELALUI SOSIALISASI PROGRAM SEKOLAH PEDULI DAN BERBUDAYA LINGKUNGAN - Ratna Widyaningrum Anggit Grahito Wicaksono (Lembaga Penelitian dan Pengabdian Masyarakat, 2018)
This community service aims to (1) provide understanding in the preparation of learning tools that are integrated with environmental education, (2) socialize innovative programs as an effort to realize the school’s cares and cultured environment, and (3) inculcate the attitude of environmental concern and scientific attitude to students of elementary school. The place of the community service is done in SDN Prawit I No. 69 Surakarta. Methods of implementation of community service include: (1) the approach method undertaken from the survey, licensing and motivation stages for the teacher to be trained (2) the method of program implementation, including the preliminary stage, the socialization and audience stage, the implementation stage and the final evaluation stage. The expected output targets is the teacher who attended this training is able to arrange learning tools and able to realize the program to the school’s cares and cultured environment. The resulting output is educational environment-oriented learning tools, Green Club's extracurricular design, implementation program in realizing a caring and cultured school environment, and publication of community service articles in scientific journals. Based on the dedication that has been done, the teachers feel interested and start designing environmentally oriented learning tools, schools have implemented clean and healthy life behaviour, and start running programs to adiwiyata school.Keywords: Environmental Concern Attitude, Scientific Attitude, School’s Care and Cultured Environment.